Risk Factors for Mortality and Readmission After Shoulder Hemiarthroplasty for Fracture. (April 2019) - Singh, Anshuman; Schultzel, Mark; Cafri, Guy; Yian, Edward H; Dillon, Mark T; Navarro, Ronald A
Background: Limited information exists regarding mortality and readmission following proximal humerus fracture. This study examines risk factors following hemiarthroplasty for these fractures. Methods: A retrospective analysis of prospectively collected data on 788 patients treated with hemiarthroplasty for acute proximal humerus fracture from January 2005 to December 2011 was conducted. One-year mortality and 30- and 90-day hospital readmission were evaluated. Patient risk factors included age, race, gender, diabetes, American Society of Anesthesiologists (ASA) score, and body mass index. Results: One-year mortality rate was 5.2%. Patients with ASA ≥3 had 2.37 times (95% confidence interval [CI]: 1.05–5.32) greater mortality risk versus patients with ASA1/2. The 30-day readmission rate was 8.4% and at 90 days was 12.6%. Females had 0.53 risk of readmission versus males (95% CI: 0.29–0.96). Patients with ASA ≥3 had 1.79 (95% CI: 1.04–3.09) risk of 90-day readmission versus patients with ASA1/2; females had 0.52 (95% CI: 0.31–0.85) risk of readmission versus males. Increased age increased all odds ratios. Conclusions: Readmission rate after hemiarthroplasty for proximal humerus fracture is significant both at 30 and 90 days and is higher in males. Age and ASA ≥3 correlate with this. Diabetes and obesity were not significant risk factors for readmission or mortality.